Developing internal power and external power for development of the proven, happy country following Ho Chi Minh thought - Dương Thị Thanh Xuân (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Throughout his life, Ho Chi Minh always pursued the aspiration to build and develop a prosperous and happy country. To realize that aspiration, Ho Chi Minh considered the promotion of internal resources and taking advantage of external forces to hold the top positions of importance. The article focuses on analyzing Ho Chi Minh’s thought on promoting internal resources and taking advantage of external forces to build and develop the country and draw lessons learned in studying and following that thought in the current period